Discrete changes in the frequency and functions of autobiographical reminiscence in Huntington's disease. Issue 10 (26th November 2019) - Carmichael, Anna M.; Irish, Muireann; Glikmann-Johnston, Yifat; Stout, Julie C.
ABSTRACT: Autobiographical memory is widely posited to serve self, social and directive functions. Recent evidence suggests marked autobiographical memory impairments in Huntington's disease (HD), however, no study to date has determined how the perceived functions of autobiographical reminiscence may be altered in HD. The current study aimed to assess the self-reported frequency and function of autobiographical reminiscence in HD. We assessed autobiographical reminiscence in late premanifest ( n = 16) and early stage HD ( n = 14), relative to healthy controls ( n = 30). Participants completed the Thinking About Life Experiences Scale Revised (TALE-R), which measures three putative functions of autobiographical memory (self, social, directive). People with manifest HD reported talking less frequently about the past compared to controls. In contrast, no group differences were found in terms of thinking about the past. Manifest HD participants further reported using their autobiographical memories for social functions less frequently compared to controls. No other group differences were evident in terms of self or directive functions of autobiographical memory. These self-report findings complement recent reports of autobiographical memory disruption on performance-based tasks in HD. Future studies exploring how changes in autobiographical reminiscence impact a sense of self continuity in HD will be important in this regard.